The environmental awareness character of elementary school students in the Kahayan River basin: Comparative study in rural and urban areas - Sunarno, Ali; Suryadi, Suryadi; Karliani, Eli; Sangalang, Ronald Hadibowo (Universitas Negeri Malang, 2024)
This study compares the environmental awareness character of elementary school students in the Kahayan River Basin, Central Kalimantan Province, who live in rural and urban areas. It is a quantitative study using survey data collection methods. The survey was conducted on 60 students: 30 students from SDN Bukit Rawi 1, located in a rural area, and 30 students from SDN Percobaan Palangka Raya, in an urban area. The survey used a questionnaire containing 20 statements with five answer options, using a Likert scale. The collected data is then analyzed using descriptive percentage analysis. The results showed that students living in rural areas of the Kahayan River Basin had better environmental awareness than those living in urban areas. The majority, 70 percent of rural students, demonstrated